FREQUENCY OF MYOCARDITIS IN COVID-19 PATIENTS - Islam, Shams Ul; Zahra, Dur -e-; Shabbir, Muhammad; Khan, Sajid; Akhtar, Najeeb; Khan, Aleena; Shaheen, Zeenat; Amin, Fazal; Siddique, Muhammad Bilal; Siddiqui, Abdul Hameed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine frequency of myocarditis in COVID-19 patients. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Institute of Cardiology-National Institute of Heart Diseases (AFIC-NIHD), Rawalpindi and Pak Emirates Military Hospital (PEMH), Rawalpindi, from Dec 2020 to May 2021. Methodology: A total of 143 hospitalized patients who had tested positive for COVID-19 infection via RT-PCR were included in the study. Patients with pre-existing cardiac conditions were excluded. All patients underwent transthoracic echocardiography and their ejection fractions were recorded. Meticulous testing for the inflammatory markers including CRP, serum ferritin, procalcitonin and interleukin-6 (IL-6) and cardiac biomarker (NT-pro-BNP) was carried out. The data was recorded on a specially designed questionnaire and later transferred to SPSS-23 for analysis. Myocarditis was diagnosed on the basis of reduced Ejection Fraction or raised NT pro BNP or both in a person without any known cardiac pathologies before getting COVID-19. Results: Out of total 143 COVID-19 patients included in the study, 24 patients (16.8%) developed myocarditis. The frequency of myocarditis in COVID-19 positive male population was 14.6% (10.5% of all myocarditis cases) and that of female population was 22.5% (6.3% of all myocarditis cases). The raised pro-inflammatory markers IL-6 and CRP were significantly associated with development of myocarditis while ferritin was not significantly associated. Only 28% of the study population recovered and got discharged from the hospital, however, there were no survivors among those who developed myocarditis. Conclusion: Myocarditis is a serious complication of COVID-19 and directly linked to increased mortality risk. There is an increasing need to perform serial assays for the inflammatory as well as cardiac biomarkers including IL-6, Trop-I and NTpro-BNP for early detection and prompt treatment of this not so uncommon complication.